How Moments Become Movements: Shared Outrage, Group Cohesion, and the Lion That Went Viral - Buhrmester, Michael D.; Burnham, Dawn; Johnson, Dominic D. P.; Curry, Oliver S.; Macdonald, David W.; Whitehouse, Harvey (Frontiers in Ecology and Evolution, 2018)
Can moments of viral media activity transform into enduring activist movements? The killing of Cecil the lion by a trophy hunter in Zimbabwe in 2015 attracted global attention and generated enduring conservation activism in the form of monetary donations to the research unit that was studying him (WildCRU). Utilizing a longitudinal survey design, we found that intensely dysphoric reactions to Cecil’s death triggered especially strong social cohesion (i.e., “identity fusion”) amongst donors. Over a six-month period, identity fusion to WildCRU increased amongst donors. In addition, in line with an emerging psychological model of the experiential antecedents of identity fusion, cohesion amongst donors increased most for those who continued to reflect deeply on Cecil’s death and felt his death to be a central event in their own lives. Our results highlight the profound capabilities of humans to commit resources to supporting others who are distant in space and time, unrelated culturally or biologically, and even (as in this case) belonging to another species altogether. In addition, our findings add to recent interdisciplinary work uncovering the precise social mechanisms by which intense group cohesion develops.